LIBERAL FEMINISM OF THE MAIN CHARACTERS IN MIRROR MIRROR MOVIE BASED ON SOCIOLOGICAL APPROACH - euis - meinawati; Irma Sukma Dewi (LPPM Universitas Bina Sarana Informatika, 2017)
The research is to know liberal feminism of main characters that occur in Mirror Mirror movie. Based on the problems it can be formulated into the general research question; How is the role a liberal feminism in the movie, how is the gender equality appear in the mirror mirror movie, how is the influence of a liberal feminism in the mirror mirror movie based on sociological approach. Descriptive qualitative method is used to do the research, in which the data is analyzed through the used of the dialogue and picture. To get information means collect the data like watching the movie and searching the related literature. Learn, collect, and summarize the redesign reference books related to the preparation of this to get data and information as needed. Analysis of mirror mirror movie used by Hollow’s theory for the liberal feminism in the mirror mirror movie. Mulia’s theory for the gender equality appear in the the mirror mirror movie. Mooney, knox, and Schacht for the liberal feminism based on sociological approach. Finding the data analysis are: (1) the role a liberal feminism is the movie is the natural biological traits of men and women. (2) gender equality shows cultural concepts that appear the role, behavior, mentality, and emotional characteristic between men and women. (3) the influence of a liberal feminism based on sociological approach are the symbolic interactionism, functionalism, and conflict theory.